Apparent rarity of diminazene-resistant trypanosomes in goats infected with a diminazene-resistant population of Trypanosoma congolense - Mamman, M.; Williams, D.J.L.; Murphy, N.B.; Peregrine, A.S. (Elsevier, 1995)
Experiments were carried out in goats to determine the frequency with which diminazene-resistant trypanosomes occur in parasite populations before and after the intramuscular treatment of the goats with diminazene aceturate. Trypanosoma congolense IL3274, a diminazene-resistant clone, was used to initiate infections in three groups of five goats. The goats in the first group were treated with diminazene aceturate at a dose of 7.0 mg kg -1 body weight within 10 seconds of infection; one of the goats was cured. All of the second group, which received no treatment, became parasitaemic. The third group of goats recieved the same dose of drug as the first group but three days after all of them were first detected parasitaemic; trypanosomes reappeared in all the five goats. When this third group was treated, the frequency of trypanosomes resistant to the drug dosage was estimated to be less than one in 10 cube. The parasites which reappeared after the treatment of these animals were used to infect two additional groups of five goats intravenously. The goats in one group were treated with the same dose of drug as before, within 10 seconds of infection and were all cured. In contrast, the five goats in the second, untreated, group became parasitaemic. Finally , when the goats in which the infections had relapsed were retreated with diminazene aceturate at the same dose rate, the level of parasitaemia temporarily decreased by at least 10 cube trypanosomes ml-1. These findings suggest that diminazene-resistant T congolense occur at low levels in trypanosome populations despite attempts to select for a population resistant to the dose of drug used.